Thee Psychick Bible : Thee Apocryphal Sciptures Ov Genesis Breyer P-Orrige and Thee Third Mind Ov Thee Temple Ov Psychick Youth. - P-Orridge, Genesis, 1950-2020 (Feral House, 2009)
Thee Temple ov Psychick Youth (TOPY) will be remembered for its crucial influence on youth culture throughout the 1980s, popularizing tattooing, body piercing, "acid house" raves, and other ahead-of-the-curve cultic flirtations and investigations. Its leader was Genesis P-Orridge, co-founder of Psychick TV and Throbbing Gristle, the band that created the industrial music genre. Included within this handsome limited signed 544 page hardcover sewn-bound ribbon-augmented bible are TOPY's apocryphal scriptures, decades-worth of updates, making this, is author Genesis Breyer P-Orridge put.